Spontaneous Maturation of Neuroblastoma to Ganglioneuroma: Two Case Studies. (1st November 2016) - Yao, Zhi-Gang; Liu, Xiu-Mei; Qin, Ye-Jun
ABSTRACT: We describe two children with ganglioneuroma (GN) likely originating from incompletely resected neuroblastoma (NB) during infancy, stages 2A and 2B, who did not undergo postoperative adjuvant chemotherapies. Both NB tumors had no MYCN amplification, had TrKA but no TrkB expression, and by TUNEL had apoptosis. These findings may have contributed to spontaneous maturation of the residual primary NB and hence the favorable prognosis, which suggests surgery alone might be the sufficient initial therapy for low-risk patients.